2021
DOI: 10.1111/mec.16133
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals Culex mosquito virome diversity and Japanese encephalitis genotype V in the Republic of Korea

Abstract: There has been a dramatic increase in emerging and re-emerging viruses of public health significance, with an estimated 60%-75% occurring from zoonotic origin, and up to one third of those being vector-borne (Jones et al., 2008;Wilson et al., 2020). Arboviruses, mosquitos in particular, represent a substantial and mostly unexplored virus reservoir of health and ecological relevance. In addition to vectoring human pathogens such as dengue, Zika, West Nile, chikungunya, and Japanese encephalitis (JEV) viruses (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…JEV genotype shift may be occurring in the ROK. Initially, the prevalent JEV genotype was identified as Genotype III until approximately 1990s when it shifted to Genotype I, and it may be shifting once again to Genotype V, which was first identified in 2010 (Sanborn et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JEV genotype shift may be occurring in the ROK. Initially, the prevalent JEV genotype was identified as Genotype III until approximately 1990s when it shifted to Genotype I, and it may be shifting once again to Genotype V, which was first identified in 2010 (Sanborn et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The cross protective capacity against other genotypes has been studied for the current Japanese encephalitis vaccine, a vaccine based on genotype III which may prevent infection for other genotypes I – IV (Elina et al, 2013). Sequence comparisons of antigenic regions of genotypes I-V indicate nucleotide (nt) similarities of less than 90% for JEV genotype I and less than 80% for JEV genotype V as compared to JEV genotype III (Sanborn et al, 2021). Serum studies have shown, JEV genotype III inactivated vaccines neutralize JEV genotype I viruses, but with reduced efficiency (Mulvey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…G5 JEV sequences were identified in mosquito surveillance during 2012 to 2018. Next-generation sequencing in mosquitoes indicated that G5 JEV is circulating in Pyeongtaek and Seoul and may become the dominant JEV genotype in Korea [32,33]. The third G5 JEV strain (K15P38) was isolated from the convalescent cerebrospinal fluid of a 27-year-old woman who had been vaccinated against JE in Korea in 2015 [34].…”
Section: G5 Jevmentioning
confidence: 99%
“…2021; Sanborn et al . 2021). Although the transmission rate of diseases spread by these vectors is largely dependent on vector competence (Fall et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals of the Culex pipiens complex in the ROK have been reported as the Culex pipiens complex or recognized as Cx. p. pallens without identifying the subspecies (Chatterjee et al 2021;Jung et al 2021;Lim et al 2021;Sanborn et al 2021). Although the transmission rate of diseases spread by these vectors is largely dependent on vector competence (Fall et al 2014), it has not yet been properly evaluated, as it is difficult to distinguish their morphologies (Mohammed et al 2021).…”
Section: Introductionmentioning
confidence: 99%